Modelagem cinemática do manipulador robótico IRB 8700 - Oliveira, Alex Rodrigo Monteiro de [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In this work, robotics approaches were carried out since its introduction, robotic importance, its applications in the market, robotic manipulators, their types, anatomy and kinematic analysis of the IRB 8700.The Denavit-Hatenberg method was applied to solve the direct kinematics and for the indirect kinematics, the kinematic decoupling, inverse position kinematics and inverse rotation kinematics methods were applied. It is concluded that not only for the manipulator in question, the methods used serve as a basis for the analysis of robotic manipulators in general, adding knowledge and parameters necessary for the development of robotic manipulators.

Neste trabalho, realizaram-se abordagens da robótica desde sua introdução, importância robótica, suas aplicações no mercado, manipuladores robóticos, seus tipos, anatomia e anáise cinemática do IRB 8700. Aplicaram-se método de Denavit-Hatenberg para resulução da cinemátca direta e para a cinemátca indireta, os métodos de desacoplamento cinemático, cinemática inversa de posição e cinemática inversa de rotação. Conclui-se que não só para o manipulador em questão, os métodos utilizados servem de base para análise de manipuladores robóticos em geral, agregando-se conhecimentos e parâmetros necessários para desenvolvimentos de manipuladores robóticos.
Kinematic modeling of the IRB 8700 robotic manipulator
Keywords: Robotics; Manipulator; Cinematic analysis; Robótica; Manipulador; Análise cinemática